Distinct patterns of inflammation in the airway lumen and bronchial mucosa of children with cystic fibrosis. Issue 2 (18th October 2011) - Regamey, Nicolas; Tsartsali, Lemonia; Hilliard, Tom N; Fuchs, Oliver; Tan, Hui-Leng; Zhu, Jie; Qiu, Yu-Sheng; Alton, Eric W F W; Jeffery, Peter K; Bush, Andrew; Davies, Jane C
Abstract : Background: Studies in cystic fibrosis (CF) generally focus on inflammation present in the airway lumen. Little is known about inflammation occurring in the airway wall, the site ultimately destroyed in end-stage disease. Objective: To test the hypothesis that inflammatory patterns in the lumen do not reflect those in the airway wall of children with CF. Methods: Bronchoalveolar lavage (BAL) fluid and endobronchial biopsies were obtained from 46 children with CF and 16 disease-free controls. BAL cell differential was assessed using May-Gruenwald-stained cytospins. Area profile counts of bronchial tissue immunopositive inflammatory cells were determined. Results: BAL fluid from children with CF had a predominance of neutrophils compared with controls (median 810×10 3 /ml vs 1×10 3 /ml, p<0.0001). In contrast, subepithelial bronchial tissue from children with CF was characterised by a predominance of lymphocytes (median 961 vs 717 cells/mm 2, p=0.014), of which 82% were (CD3) T lymphocytes. In chest exacerbations, BAL fluid from children with CF had more inflammatory cells of all types compared with those with stable disease whereas, in biopsies, only the numbers of lymphocytes and macrophages, but not of neutrophils, were higher. A positive culture of Pseudomonas aeruginosa was associated with higher numbers of T lymphocytes in subepithelial bronchial tissue (median 1174 vs 714 cells/mm 2, p=0.029), but no changes were seen in BAL fluid. Cell counts in BAL fluid and biopsies were positively correlated with age but were unrelated to each other. Conclusion: The inflammatory response in the CF airway is compartmentalised. In contrast to the neutrophil-dominated inflammation present in the airway lumen, the bronchial mucosa is characterised by the recruitment and accumulation of lymphocytes.